Public Complaint Management Information System Based on Complaint Topic Classification Using the Naive Bayes Model - Nasrulloh, Wildan Khotibul Umam; Hermanto, Cahyo; Jamaludin, Ikbal; Emalia, Lilis (Journal of Economics, Management, and Entrepreneurship, 2025)
Superior public service is an essential component of community life. Pasirkaliki Village faces considerable hurdles in managing public grievances, including inefficiencies and complications in prioritizing complaints according to their urgency. This research proposes the creation of a Public Complaint Management Information System utilising the Naive Bayes method within the CodeIgniter Framework to address these challenges. The Naive Bayes method is selected for its efficacy in classifying data, enabling the identification of patterns and trends in incoming complaints. This system aims to enhance the efficiency and precision of complaint management, deliver swifter and more accurate responses, and ultimately improve public satisfaction with the services. The findings of this research are anticipated to enhance the provision of responsive and high-quality public services in Pasirkaliki Village.